Child-Friendly Curriculum Implementation During Pandemic Covid-19 - Hasanah, Uswatun; Sibilana, Annas Ribab; Nurhidayati, Nurhidayati (Martabat: Jurnal Perempuan dan Anak, 2020)
The curriculum as the most important element in the world of education continues to change. The curriculum can also change if a disaster occurs in an area such as the Covid-19 pandemic that occurred in Indonesia. The existence of the Covid-19 pandemic requires education managers in each agency to innovate in compiling a curriculum that can be implemented safely, effectively and efficiently, because the safety and comfort of students in learning are also a separate consideration in implementing learning during a pandemic. Like the child-friendly curriculum implemented at MI Barokah At-Tahdzib. This study aims to explain the implementation of the child-friendly curriculum at MI Barokah At-Tahdzib during the pandemic Covid-19. The method used is a qualitative method with interactive model data analysis techniques. The results of this study indicate that the child-friendly curriculum is implemented through three activities, first implementing learning while still paying attention to health protocols, second, creating a study group consisting of 11 children to implement social and physical distancing with a learning duration of 1.5-2 hours, The third assessment of cognitive and psychomotor aspects of learning is carried out in a network through WhatsApp and Google Form, while the assessment of affective aspects is carried out using observation techniques.